Volume 2A: Turbomachinery 2017
DOI: 10.1115/gt2017-63616
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Individual High-Pressure Turbine Rotor Purge Flows on Turbine Center Frame Aerodynamics

Abstract: This paper presents an experimental study of the impact of individual high-pressure turbine purge flows on the main flow in a downstream turbine center frame duct. Measurements were carried out in a product-representative one and a half stage turbine test setup, installed in the Transonic Test Turbine Facility at Graz University of Technology. The rig allows testing at engine-relevant flow conditions, matching Mach, Reynolds, and Strouhal number at the inlet of the turbine center frame. The reference case feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The measurement campaign is carried out in its entirety in the Transonic Test Turbine Facility (TTTF) of the Graz University of Technology (Institute of Thermal Turbomachinery and Machine Dynamics, ITTM). The TTTF is a dual-spool, continuous, open-circuit test bench historically devoted to the aerothermal investigation of intermediate turbine frames [19][20][21]. The main flow is supplied to the turbine by a 3 MW compression station, while a 560 kW suction blower, placed downstream of the test section, allows to decrease and stabilize the backpressure against ambient condition variations.…”
Section: Facility and Test Vehiclementioning
confidence: 99%
“…The measurement campaign is carried out in its entirety in the Transonic Test Turbine Facility (TTTF) of the Graz University of Technology (Institute of Thermal Turbomachinery and Machine Dynamics, ITTM). The TTTF is a dual-spool, continuous, open-circuit test bench historically devoted to the aerothermal investigation of intermediate turbine frames [19][20][21]. The main flow is supplied to the turbine by a 3 MW compression station, while a 560 kW suction blower, placed downstream of the test section, allows to decrease and stabilize the backpressure against ambient condition variations.…”
Section: Facility and Test Vehiclementioning
confidence: 99%
“…[3][4][5] In general, the rim seal flow is considered to decrease blade loading of the rotor and intensify the secondary flow loss which deteriorates the aerodynamic performance. [6][7][8] Therefore, it is essential to investigate the impact of the rim seal flow on the mainstream for elucidating the flow and loss mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Schrewe et al [18] performed an efficiency measurement and found an efficiency drop with the increase of rim seal mass flow rate in a two-stage low-pressure turbine. Zerobin et al [19,20] investigated the influence of four individual purge flows on the aerodynamic performance of turbine center frames with a 1.5-stage turbine test setup. Purge flow injection intensified secondary flow structures in main annulus flow and increased pressure fluctuations on the platform.…”
Section: Introductionmentioning
confidence: 99%